White but not quite: Central Europe's illiberal revolt - Kalmár, Ivan Davidson (Bristol University Press, 2022)
The response to neoliberal globalisation in Central Europe has led to populism arising from its brutal transition to capitalism. Kalmar uses examples from popular culture to sport to reject as racist the idea that Central Europe's cultures are incompatible with liberal democracy